Techniques and Approaches to Utilize Nitrogen Fixing Systems in Forestry Plantation Programmes - Pokhriyal, T. C.; Mathani, G. P. (Indian Forester, 1989)
The exploitation of biological nitrogen fixation presently demands an increased use of Nitrogen fixing tree specing and other symbiotic systems in silvicultural practices in context to meet the stupendous targets of afforestation of wastelands and fuel wood production. In tbe present article an attempt has been made to discuss tbe usefulness of the techniques and approaches to utilize nitrogen fixing systems in forestry plantation programmes.